2008
DOI: 10.1007/s10886-008-9436-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human-Derived Volatile Chemicals that Interfere with Attraction of Aedes aegypti Mosquitoes

Abstract: It is known that human individuals show different levels of attractiveness to mosquitoes. In this study, we investigated the chemical basis for low attractiveness. We recorded behaviors of Aedes aegypti toward the hands of human volunteers and toward the volatile chemicals produced by their bodies. Some individuals, and their corresponding volatiles, elicited low upwind flight, relative attraction, and probing activity. Analyzing the components by gas chromatography coupled to electrophysiological recordings f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
246
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(259 citation statements)
references
References 41 publications
10
246
3
Order By: Relevance
“…Detailed analysis of human skin emanations and their relationship to mosquito attraction have been already reported (19)(20)(21)(22)(23), but our aim was to determine whether DEET affects the release of physiologically relevant compounds. Some of the major human-derived compounds suppressed by DEET have been previously reported as attractants or repellents (19)(20)(21)(22)(23) and most of them are indeed electrophysiologically active (data not shown). Of notice, the skin of the human subject was exhaustively washed with warm water before the experiments and none of the compounds detected were observed in the soap regularly used by the human subject (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed analysis of human skin emanations and their relationship to mosquito attraction have been already reported (19)(20)(21)(22)(23), but our aim was to determine whether DEET affects the release of physiologically relevant compounds. Some of the major human-derived compounds suppressed by DEET have been previously reported as attractants or repellents (19)(20)(21)(22)(23) and most of them are indeed electrophysiologically active (data not shown). Of notice, the skin of the human subject was exhaustively washed with warm water before the experiments and none of the compounds detected were observed in the soap regularly used by the human subject (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our case it leads to an alteration of the host chemical profile and a possible interference with attraction. In this context, it may be considered a ''masking'' effect (21,24,25) on the release rather than on the reception of chemical signals.…”
Section: Resultsmentioning
confidence: 99%
“…Nonanal also elicited EAG and behavioral response in host seeking adult Ae. aegypti females (35). Although nonanal was found in fresh and incubated sweat samples, no EAG activity was observed in Anopheles gambiae (36).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that 2-ethyl-1-hexanol is a precursor of the common plasticiser dioctyl phthalate (Thorat et al 1992) and may, therefore, be an artefact or pollutant. However The ketone, 6-methyl-5-hepten-2-one, has also been shown to regulate differential attraction of C. impunctatus (Logan et al 2009) and of the mosquito Aedes egypti (Logan et al 2008) to humans, as well as of the horn fly, Heamatobia irritans, to cattle (Birkett et al 2004). Similar to these studies, we observed attraction, behavioral inhibition or nonpreference depending on the concentration tested.…”
Section: Behavioral Assaymentioning
confidence: 99%